Mitochondria as a target in treatment - Frantz, Marie-Céline (2010)
Mitochondria are key organelles that perform essential cellular functions and play pivotal roles in cell death and survival signaling. Hence, they represent an attractive target for drugs to treat metabolic, degenerative and hyperproliferative diseases. Targeting mitochondria with organelle-specific agents or prodrugs has proven to be an effective therapeutic strategy. More specifically, controling the cellular ROS balance via selective delivery of an antioxidant “payload” into mitochondria is an elegant emerging therapeutic concept. Herein, we review the recent medicinal chemistry and clinical data of these exploratory strategies which should point the way for future generations of therapeutics.